2005
DOI: 10.1161/01.hyp.0000172621.68061.22
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Homologous Internalization of the Angiotensin II Type-1 Receptor Induced by G-Protein–Independent Signals

Abstract: Abstract-Internalization of a G-protein-coupled receptor (GPCR) is essential to the desensitization, endocytosis, and signal transduction of the receptor. It has been the general view that conventional homologous internalization of a GPCR requires activation of the G-protein(s) coupled to the receptor. However, whether and how GPCR-mediated G-protein-independent signals trigger receptor internalization remains unknown, although G-protein-independent internalization has been reported. Here we show that an angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 43 publications
5
28
0
Order By: Relevance
“…The result demonstrated that mutation of negatively charged aspartic acid at position 104 to positively charged amino acid of lysine functionally inactivated the receptor by uncoupling with G protein. Earlier, other similar types of investigation has been reported in β 2 -adrenergic (Chung et al 1988), α 2A adrenergic (Wang et al 1991) and AT 1 (Feng et al 2005) receptor due to mutation at conserved aspartic acid. On the other hand, the mutant Asp104Ala showed the higher basal level of cAMP production without agonistinduced stimulation, which might be another possible reason for demonstrating this abnormal signaling characteristic of receptor.…”
Section: Discussionsupporting
confidence: 62%
“…The result demonstrated that mutation of negatively charged aspartic acid at position 104 to positively charged amino acid of lysine functionally inactivated the receptor by uncoupling with G protein. Earlier, other similar types of investigation has been reported in β 2 -adrenergic (Chung et al 1988), α 2A adrenergic (Wang et al 1991) and AT 1 (Feng et al 2005) receptor due to mutation at conserved aspartic acid. On the other hand, the mutant Asp104Ala showed the higher basal level of cAMP production without agonistinduced stimulation, which might be another possible reason for demonstrating this abnormal signaling characteristic of receptor.…”
Section: Discussionsupporting
confidence: 62%
“…The present study demonstrated the correlation between endocytosis and signal transduction of AT 1 receptors due to its site directed mutagenesis. Homologous internalization of GPCRs is an active process that requires specific ligand binding, conformational changes of the receptor, and signal transduction initiated by the activated receptor (13). To determine the possible reason for the behavior of the N111G mutant of the AT 1 receptor in signaling transduction, the present study investigated internalization in terms of cell localization of the receptor protein.…”
mentioning
confidence: 99%
“…Agonist binding to a GPCR induces conformational changes in the receptor, leading to activation of Gαβγ heterotrimers (10). One function of the activated Gproteins is to activate GPCR kinases (GRKs) that in turn phosphorylate the specific receptor for desensitization.…”
mentioning
confidence: 99%